Cost-effectiveness of colorectal cancer screening in Germany: current endoscopic and fecal testing strategies versus plasma methylated Septin 9 DNA - Ladabaum, Uri; Alvarez-Osorio, Lourdes; Rösch, Thomas; Brueggenjuergen, Bernd (Endoscopy International Open, 2014)
Background and study aims: Colorectal cancer (CRC) screening strategies in Germany include guaiac-based fecal occult blood testing (gFOBT) starting at age 50 and a switch to colonoscopy at age 55 or continued gFOBT testing, but screening utilization is limited. Blood-based biomarkers, such as methylated Septin 9 DNA (mSEPT9), may improve screening rates. We performed a cost-effectiveness analysis of current and emerging CRC screening strategies in Germany.Methods: Using a validated Markov model, we compared annual gFOBT for ages 50 through 54 followed by biennial testing until age 75 (FOBT) or by colonoscopy at ages 55 and 65 (FOBT/COLO 55,65), substitution of fecal immunochemical testing (FIT) for gFOBT (FIT, FIT/COLO 55,65), and annual or biennial plasma mSEPT9 testing. We also considered persons who utilize only colonoscopy and varied age at colonoscopy utilization.Results: The current strategies were more effective and less costly than no screening. FIT was more effective and less costly than mSEPT9 testing. FIT/COLO 55,65 cost €12 200 per quality-adjusted life-years gained in comparison with FIT. mSEPT9-based screening was cost-effective in comparison with no screening but was dominated by other cost-saving strategies. Differential screening utilization and adherence greatly affected incremental results between strategies. In probabilistic analyses, FIT was preferred in 49 % and FIT/COLO 55,65 in 47 % of iterations.Conclusion: Currently available CRC screening strategies in Germany, including hybrid fecal testing/colonoscopy, are likely to be cost-saving. Current strategies appear superior to mSEPT9-based screening. The impact of blood-based biomarkers is likely to depend on utilization and adherence as much as on test performance characteristics and cost.